Engaging Families in Adult Cardiovascular Care: A Scientific Statement From the American Heart Association - Goldfarb, Michael J.; Bechtel, Christine; Capers, Quinn; de Velasco, Ann; Dodson, John A.; Jackson, Jamie L.; Kitko, Lisa; Piña, Ileana L.; Rayner‐Hartley, Erin; Wenger, Nanette K.; Gulati, Martha (Journal of the American Heart Association, 2022)
Family engagement empowers family members to become active partners in care delivery. Family members increasingly expect and wish to participate in care and be involved in the decision‐making process. The goal of engaging families in care is to improve the care experience to achieve better outcomes for both patients and family members. There is emerging evidence that engaging family members in care improves person‐ and family‐important outcomes. Engaging families in adult cardiovascular care involves a paradigm shift in the current organization and delivery of both acute and chronic cardiac care. Many cardiovascular health care professionals have limited awareness of the role and potential benefits of family engagement in care. Additionally, many fail to identify opportunities to engage family members. There is currently little guidance on family engagement in any aspect of cardiovascular care. The objective of this statement is to inform health care professionals and stakeholders about the importance of family engagement in cardiovascular care. This scientific statement will describe the rationale for engaging families in adult cardiovascular care, outline opportunities and challenges, highlight knowledge gaps, and provide suggestions to cardiovascular clinicians on how to integrate family members into the health care team.